STUDY OF TWACHA SHARIR WITH SPECIAL REFERENCE TO CHARAKOKTA CHATURTHA STHARIYA (FOURTH LAYER) DADRU VYADHI (AYUSHDHARA, 2020)
Twacha (skin) is one of the important Dnyanendriya (sense organ) which covers all other Indriyas and whole body. There are many doubts and unknown things regarding Ayurvedokta Twacha. Charaka has described six layers and the corresponding diseases of that layer of the Twacha. Out of these, the fourth layer is the seat of manifestation of Dadru Vyadhi. Also signs and symptoms of Dadru shows similarities with the signs and symptoms of tinea infection according to modern science. Hence to simplify above described terminologies regarding Twacha present study was carried out.30 patients having signs and symptoms of Dadru were selected to rule out whether there is any extent of Dadru Vyadhi other than fourth layer with the help of skin biopsy. Also to establish relation between Dadru and likewise disease tinea infection of fourth layer i.e. stratum and to study anatomico-physiological changes in skin layers in Dadru Vyadhi with the help of histopathological study. From the present work done it was observed that the anatomico-physiological changes were found upto the fourth layer of skin which Charaka has already stated. Most of the signs and symptoms of Dadru patients found similar to tinea corporis infection which demonstrate the relation between Dadru and tinea infection.